Neoliberal feminism: The neoliberal rhetoric on feminism by Australian political actors. Issue 8 (21st September 2018) - Colley, Linda; White, Catherine
Abstract : Feminism seems to be experiencing a resurgence. This research examines an Australian case where this resurgence produces some bizarre outcomes and an uncomfortable mix of moderate and neoliberal feminisms, as conservative women distance themselves from the term feminist and conservative men embrace it. We rhetorically analyse the discourse of four conservative leaders using an ideographic analysis to reveal how political actors evoke ideologically laden terminology to support specific courses of action. For the conservative women, the ideograph feminist was too heavily laden with history. A more feminine‐liberal political discourse allowed them to explain their own success in individual terms and, by substituting support for feminism with a broader gender equality agenda, they could explain the government's policy approach of individualized rather than collective or state support to advance the needs of women. They are articulating a postfeminism sensibility themselves and neoliberal feminist other. For the conservative men, the ideograph feminist did not reflect on their own personal success or careers; they were happy to embrace it for purely political purposes to advance their standing with the voting public and saw no significance in terms of the government's policy approach of neoliberal feminism.